Comprehensive analysis of glycerolipid dynamics during tobacco pollen germination and pollen tube growth - Serrano, Natalia; Pejchar, Přemysl; Soukupová, Hana; Hubálek, Martin; Potocký, Martin (Frontiers in Plant Science, 2022)
Pollen germination and subsequent pollen tube elongation are essential for successful land plant reproduction. These processes are achieved through well-documented activation of membrane trafficking and cell metabolism. Despite this, our knowledge of the dynamics of cellular phospholipids remains scarce. Here we present the turnover of the glycerolipid composition during the establishment of cell polarity and elongation processes in tobacco pollen and show the lipid composition of pollen plasma membrane-enriched fraction for the first time. To achieve this, we have combined several techniques, such as lipidomics, plasma membrane isolation, and live-cell microscopy, and performed a study with different time points during the pollen germination and pollen tube growth. Our results showed that tobacco pollen tubes undergo substantial changes in their whole-cell lipid composition during the pollen germination and growth, finding differences in most of the glycerolipids analyzed. Notably, while lysophospholipid levels decrease during germination and growth, phosphatidic acid increases significantly at cell polarity establishment and continues with similar abundance in cell elongation. We corroborated these findings by measuring several phospholipase activities in situ. We also observed that lysophospholipids and phosphatidic acid are more abundant in the plasma membrane-enriched fraction than that in the whole cell. Our results support the important role for the phosphatidic acid in the establishment and maintenance of cellular polarity in tobacco pollen tubes and indicate that plasma membrane lysophospholipids may be involved in pollen germination.